Voids, layers, and the first sharp diffraction peak in ZnCl2 - Wilson, M; Madden, P (1998)
The origin of the first-sharp diffraction peak (FSDP) in supercooled liquid ZnCl2 (a network-forming, intermediate strength fluid) is studied by computer simulation. Measures are introduced to characterize voids in the spatial distribution of cations and the existence of transient layered structures and to clarify their role in producing the FSDP. It is shown that the position of the FSDP is set by the mean intervoid separation and that its intensity is due to density fluctuations with a layered character even well above the glass transition.